The Optimization of Silica-Based Composite Membrane from Volcanic Ash of Mount Sinabung, Titanium Dioxide, and Polyvinyl Alcohol for River Water Treatment through Photocatalyst Process - Timbangen Sembiring; Zuriah Sitorus; Syahrul Humaidi; Fynnisa Zebua; Rahmadsyah Rahmadsyah; Moraida Hasanah (Universitas Gadjah Mada, 2022)
The application of composite membranes consisting of SiO2 from the volcanic ash of Mount Sinabung, TiO2, and PVA on a laboratory scale has been investigated to improve the Silau River’s water quality in Asahan Regency. The purpose of this study is to determine the optimal combination of SiO2, TiO2, and PVA for treating river water to minimize its heavy metal content and color intensity to achieve clean water requirements. The membranes were prepared by drop-casting with varied compositions of PVA/40TiO2/60SiO2, PVA/60TiO2/40SiO2, PVA/80TiO2/20SiO2, and PVA/100TiO2/0SiO2. PVA was dissolved in aquadest, mixed with SiO2 and TiO2, then imprinted and dried for 24 h at 50 °C. A photocatalyst test was performed on each composition variation to see how the Silau River water’s color changed over time. The PVA/80TiO2/20SiO2 membrane’s composition fluctuated the highest during photocatalyst testing, with 45.95% degradation. The parameter results on the Silau River water test, namely turbidity, color, and chromium values, were reduced by photocatalysis of a PVA/80TiO2/20SiO2 composite membrane to 16 NTU, 30 TCU, and 0.013 mg/L, respectively. These results met the clean water quality criteria specified by Minister of Health of the Republic of Indonesia Decree No. 416/MENKES/PER/IX/1990.